Genetic Basis for Resistance Against Viral Nervous Necrosis: GWAS and Potential of Genomic Prediction Explored in Farmed European Sea Bass (Dicentrarchus labrax) - Vela-Avitúa, Sergio; Thorland, Ingunn; Bakopoulos, Vasileios; Papanna, Kantham; Dimitroglou, Arkadios; Kottaras, Eleftherios; Leonidas, Papaharisis; Guinand, Bruno; Tsigenopoulos, Costas S.; Aslam, Muhammad L. (Frontiers in Genetics, 2022)
Viral nervous necrosis (VNN) is an infectious disease caused by the red-spotted grouper nervous necrosis virus (RGNNV) in European sea bass and is considered a serious concern for the aquaculture industry with fry and juveniles being highly susceptible. To understand genetic basis for resistance against VNN, a survival phenotype through the challenge test against RGNNV was recorded on populations from multiple year classes (YC2016 and YC2017). A total of 4,851 individuals from 181 families were tested and a subset (n~1,535) belonging to 122 families was genotyped using a ~57K Affymetrix Axiom array. The survival against RGNNV showed low to moderate heritability with observed scale estimates of 0.18 and 0.25 obtained using pedigree vs. genomic information, respectively. The genome-wide association analysis showed a strong signal of quantitative trait loci (QTL) at LG12 which explained ~33% of the genetic variance. The QTL region contained multiple genes (ITPK1, PLK4, HSPA4L, REEP1, CHMP2, MRPL35, and SCUBE) with HSPA4L and/or REEP1 gene being highly relevant with likely effect on host response in managing disease associated symptoms. The results on accuracy of predicting breeding values presented 20 to 43% advantage in accuracy using genomic over pedigree-based information which varied across model types and applied validation schemes.